Harmful Chemicals in Soil and Risk Assessment of an Abandoned Open Dumpsite in Eastern China - Ying Huang; YongXia Li; Jian Yang; MinMin Xu; Bo Sun; FuWei Gao; Ning Wang (Journal of Chemistry)
The concentrations of pollutants in soil samples collected in and around a dumpsite in Heze, Shandong, China, were investigated, and the potential ecological and health risks of these pollutants were assessed. Seventeen soil samples from five different locations were analysed for pollution characteristics, and the target pollutants included inorganic pollutants and heavy metals as well as volatile organic compounds/semivolatile organic compounds (VOCs/SVOCs). Results showed that the mean concentration level of each pollutant from the interior area was relatively higher than that from the boundary area of the dumpsite. Inorganic pollutants and heavy metals were detected in all of the soil samples. According to potential ecological risk assessment with environmental background values of Shandong as screening values, heavy metals in majority of the samples pose low ecological risk to the ecosystem except Hg. Hg poses a considerable or very high risk because of its high levels of accumulation. In consideration of future land use pattern, human health risks derived from environmental exposure to heavy metals were assessed. Carcinogenic risk and noncarcinogenic hazards for adults are acceptable, while noncarcinogenic hazards for children exceed the safety threshold. The health risks are primarily attributed to oral exposure to As and Cr.